Flood Modelling in Muar Town Using HEC-RAS - SYED ZAKARIA, SYED MOHD FIRDAUS; MOHAMMAD RAZI, MOHD ADIB (Recent Trends in Civil Engineering and Built Environment, 2023)
Muar town Johor, as has been reported every year, has experienced seasonal floods at the end of each year from October to January at the beginning of the year. This incident has caused damages to most public property and government property such as houses, buildings, roads, and many others. The behavior of floods, the impact on the local population, and the effectiveness of man-made drainage systems in the city of Muar and the production of flood models are the major objectives of the study. The study is conducted to upgrade the existed man-made drainage system in Muar town based on the modeling that will be done with the hydrology software that is Hydrologic Engineering Centre’s River Analysis System HEC-RAS. The study is conducted by a collection of the data in the study area before performing HEC-RAS. Terrain data, geometric data, cross-section data, and flow data will be conducted one by one in the HEC-RAS before running the project. The study discovered increasing rainfall trends, which are one of the most important factors in flooding from year to year. As a result, the current drainage system will be ineffective in the future. The flood modeling can prevent the flooding to be occurred by channel modification of the drainage cross-section for all the stations that are overflowing from the bank for all the profiles.